102 ICD IMPLANTATION IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY (HCM): A LONG-TERM SINGLE CENTER EXPERIENCE. (15th December 2022) - Buongiorno, Antonia Luisa; Blandino, Alessandro; Bianchi, Francesca; Masi, Andrea Sibona; Mabritto, Barbara; Luceri, Stefania; Bongioanni, Sergio; De Rosa, Catia; Tommasello, Antonino; Parrini, Iris; Grossi, Stefano; Musumeci, Giuseppe
Abstract: Background: Subcutaneous ICD (S-ICD) is a safe and effective tool in preventing sudden cardiac death (SCD) and it has the potential to overcome the limitations of transvenous ICDs. Because of increased left ventricular mass and unpredictable electrical substrate, concerns regarding the safety and efficacy of S-ICD in hypertrophic cardiomyopathy (HCM) patients have been raised. Material and Methods: We retrospectively collected clinical data from consecutive HCM patients who underwent ICD implantation and were followed at our Cardiology Department from January 2000 to January 2022. Results: Among 702 HCM patients, 52 (7.4%) received an ICD (female, 30.7%; mean age at implantation, 49 ± 20; primary prevention, 86.5%; S-ICD, 13%; single-chamber ICD, 50%). During a mean follow up of 8 ± 5 years, 27 shocks occurred in 20 (38%) patients of which 11 appropriate shocks (AS) in 9 (17%) patients and 16 inappropriate shocks (IS) in 11 (21%) patients, respectively after 4.3 ± 3 and 5 ± 4 years. AS were due to ventricular tachycardia (7) and ventricular fibrillation (4) and occurred in 9 patients with transvenous ICD vs. 0 in S-ICD patients (100% vs. 0%, p=0.32). IS were due to AF (8), PSVT (3), sinus tachycardia (2), and oversensing (3), with a non-significant trend towards a higher rate in patients with transvenous ICD compared to those with S-ICD (33% vs 14%, p=0.41). Device-related complications (DC) were recorded in 14 (27%) patients and were secondary to lead fracture (6), pocket hematoma (3), pneumothorax (1), device malfunctioning (1), endocarditis (2), and venous thrombosis (1). Compared to S-ICD, transvenous ICD was associated with a non-significant higher risk of DC (31% vs. 0%, p=0.17). Conclusions: In HCM patients at high risk of SCD, when compared to transvenous ICD, S-ICD is related to a non-significant lower rate of IS and DC, with similar rate of AS. Further randomized studies as well as large prospective registries are needed to confirm these findings.